Porous carbon, preparation method thereof and silicon-carbon negative electrode material
By using chitosan and nano-calcium carbonate to prepare porous carbon with uniform and stable mesoporous structures, the problem of low porosity of existing porous carbon is solved, and the first Coulomb efficiency and cycle stability of silicon carbon anode materials are significantly improved.
Patent Information
- Application Number
- CN202411575422.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
AI Technical Summary
The porosity of existing porous carbon is low, which limits the diffusion path of lithium ions and reduces the transmission rate of lithium ions. It is not conducive to buffering the volume changes of silicon during charging and discharging, resulting in the cyclic stability of silicon carbon negative electrode materials and Coulun was not efficient for the first time.
Porous carbon is prepared by using chitosan and nano-calcium carbonate as raw materials and through emulsification and cross-linking, carbonization and hydrofluoric acid treatment, forming porous carbon with a uniform and stable mesoporous structure, improving its lithium ion transmission capacity and buffering silicon The ability to change volume.
The conductivity of porous carbon and the first Coulomb efficiency and cyclic stability of silicon-carbon negative electrode materials are significantly improved, the mechanical strength and electrical conductivity of the material are enhanced, the bonding force between the silicon and carbon interface is improved, and the internal resistance is reduced.
Smart Images

Figure CN119390069A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery materials, and in particular to a porous carbon and a preparation method thereof and a silicon-carbon negative electrode material. Background Art
[0002] The performance of lithium battery negative electrode materials plays a vital role in the overall performance of the battery. Although traditional graphite negative electrode materials have high cycle stability and good safety, their theoretical specific capacity is only 372 mAh / g, which is difficult to meet the development trend of high energy density batteries. Therefore, it is of great significance to develop new negative electrode materials with high specific capacity. Silicon-carbon negative electrode materials are considered to be the ideal choice for the next generation of lithium-ion battery negative electrode materials due to their high theoretical specific capacity (about 4200 mAh / g) and excellent cycle stability.
[0003] Silicon-carbon negative electrode materials are usually composed of nano-silicon particles and a porous carbon matrix. Among them, the porous carbon matrix not only provides abundant lithium storage sites, but also effectively buffers the volume change of silicon during the charge and discharge process, thereby improving the cycle stability and rate performance of the material. The current preparation method of porous carbon is usually obtained by high-temperature activation of coke and an alkaline activator. For example, a petroleum coke-based porous carbon material and its preparation method and a silicon-carbon negative electrode material are disclosed in a patent application with publication number CN109037679A. The method calcines a mixture of petroleum coke and a pore-forming agent obtained after ball milling to obtain a petroleum coke-based porous carbon material.
[0004] Although the above method is easy to operate, the porous carbon obtained has the problem of low porosity. This not only limits the diffusion path of lithium ions and reduces the transmission rate of lithium ions, but also the low porosity is not conducive to buffering the volume expansion of silicon during the charging and discharging process, which easily leads to the aggregation and shedding of silicon particles, and is not conducive to ensuring the cycle stability of silicon-carbon negative electrode materials. Summary of the invention
[0005] In order to solve the problem of low porosity of porous carbon produced by current preparation methods, the present application provides a porous carbon and a preparation method thereof and a silicon-carbon negative electrode material.
[0006] In a first aspect, the present application provides a porous carbon, which is used to prepare a silicon-carbon negative electrode material, and the preparation method comprises: Mix petroleum coke, alkaline activator and porous carbon in a mass ratio of 1:1.8-4.5:0.4-1.2 to prepare a premix; The premix is placed in a non-reactive atmosphere, and then activated, washed, dried, and crushed to obtain the premix; The porous carbon is obtained by carbonizing chitosan microspheres and treating them with hydrofluoric acid.
[0007] Petroleum coke is a carbon material with a high degree of graphitization, high mechanical strength and good stability. However, its pore structure after activation is small, and there are many micropores (less than 2nm). Such micropores are difficult to deposit silicon and the buffering effect is not obvious, which is not conducive to improving the electrical properties and cycle stability of the material. In addition, the microporous structure greatly increases the specific surface area of the porous carbon, which easily reduces the first coulombic efficiency of the silicon-carbon negative electrode material. To this end, the present application adds porous carbon prepared by carbonization of biomass materials, and its carbon source is porous microspheres prepared by emulsification and cross-linking of chitosan. After pre-carbonization, it has a rich porous structure. The porous carbon obtained after activation has good lithium ion transmission capacity and has a large number of mesoporous (2-50nm) structures, which can effectively buffer the volume change of silicon during the charge and discharge cycle, ensure the cycle stability (capacity retention rate) of the negative electrode material, and improve the first coulombic efficiency of the silicon-carbon negative electrode material.
[0008] In addition, since chitosan carbon source contains more amino groups, nitrogen-doped porous carbon can be obtained during the carbonization process, thereby improving the electrical conductivity of porous carbon and silicon-carbon materials.
[0009] It should be noted that the present application cannot avoid the generation of microporous structure. During the preparation process, the generation of pore structure does not entirely depend on the application of the above-mentioned spherical nano-calcium carbonate. The volatilization of substances and the generation of gases during the activation process, especially the reaction of alkaline activators and carbon at high temperatures, all of these factors will affect the distribution of the pore structure.
[0010] In any of the above technical solutions, the non-reactive atmosphere is a nitrogen or argon atmosphere.
[0011] In any of the above technical solutions, the porous carbon-based preparation method is as follows: Chitosan is dissolved in a dilute acid solution, and liquid paraffin, spherical nano-calcium carbonate, and an emulsifier are added, and stirred to form an emulsion system; epichlorohydrin is added to the emulsion system, and an alkaline solution is added under stirring conditions to allow the system to be cross-linked under alkaline conditions; after the reaction is completed, the chitosan microspheres are obtained by filtering, washing, and drying; the mass ratio of the chitosan to the spherical nano-calcium carbonate is 1:0.25-0.5.
[0012] Under nitrogen protection, chitosan microspheres are calcined and carbonized at 550-650°C; the carbonized microspheres are then immersed in hydrofluoric acid to remove spherical nano-calcium carbonate, and porous carbon is obtained through centrifugation, washing and drying.
[0013] In the above-mentioned preparation process, the present application adds spherical nano-calcium carbonate as a template, and after calcination and carbonization, the spherical nano-calcium carbonate is removed by hydrofluoric acid, thereby forming uniform spherical pores in the chitosan microspheres. By controlling the particle size of spherical nano-calcium carbonate, the number of micropores with negative effects can be effectively reduced and the number of effective pores can be increased. In addition, hydrofluoric acid immersion can also increase the content of active groups such as hydroxyl and carboxyl in porous carbon, promote the adsorption and deposition of silane on the surface of porous carbon, increase the proportion of nano-silicon, improve and enhance the interfacial bonding force between silicon and carbon, reduce internal resistance, and help improve the electrical properties such as the first reversible capacity and cycle stability of silicon-carbon negative electrode materials.
[0014] It should be noted that the concentration of the hydrofluoric acid should be greater than 3wt% and not higher than 6wt% to reduce carbon loss.
[0015] In any of the above technical solutions, the particle size distribution of the spherical nano-calcium carbonate is 2 to 50 nm.
[0016] Exemplarily, the particle size distribution of the spherical nano-calcium carbonate is 2-10 nm, 3-10 nm, 3-20 nm, 10-25 nm, 5-15 nm, 5-25 nm, 5-30 nm or 5-50 nm.
[0017] In any of the above technical solutions, the sphericity of the spherical nano calcium carbonate is greater than 0.8.
[0018] The above-mentioned “sphericity” means the ratio of the surface area of a sphere having the same volume as a particle to the surface area of the particle, wherein the sphericity of a perfectly spherical particle is 1. And the sphericity described in the present application is the median sphericity or average sphericity of a plurality of particles.
[0019] In any of the above technical solutions, the median particle size of the porous carbon-based material is 2 to 20 μm.
[0020] In any of the above technical solutions, the median particle size of the petroleum coke is 5 to 75 μm.
[0021] The above median particle size is the D50 particle size or the average particle size, which can be obtained by statistically analyzing at least 200 typical samples using equipment such as a scanning electron microscope, a light scattering instrument, and a light scattering instrument.
[0022] Exemplarily, the median particle size of the porous carbon is 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm or 20 μm.
[0023] In any of the above technical solutions, the roasting and carbonization time is 3 to 6 hours.
[0024] In any of the above technical solutions, the activation treatment is: heating to 280-450°C at a rate of 1-10°C / min, and treating at a constant temperature for 1-2 hours; then heating to 700-900°C at a rate of 5-10°C / min, and treating at a constant temperature for 1.5-3.5 hours.
[0025] In any of the above technical solutions, the alkaline activator is potassium hydroxide or sodium hydroxide.
[0026] In any of the above technical solutions, the deacetylation degree of the chitosan is 75-90%.
[0027] Within the above range, the deacetylation degree increases the amino content in chitosan, which helps to increase its solubility and improve the uniformity, stability and porosity of porous microspheres, and also helps to improve the mechanical strength of the cross-linked porous microspheres and the corresponding porous carbon. It should be noted that too high a deacetylation degree may lead to excessively high viscosity of the emulsion system, decreased stability, and the formation of large polymer particles, which affects the uniformity and pore structure of the final microspheres.
[0028] In any of the above technical solutions, the emulsion system contains graphite oxide powder; the mass ratio of the chitosan to the graphite oxide powder is 1:0.05-0.15; and the aspect ratio of the graphite oxide powder is 1:500-5000.
[0029] In any of the above technical solutions, the graphite oxide powder has a diameter of 0.5 to 5 μm and a thickness of 1 to 5 nm.
[0030] It should be noted that the above diameter length is the median diameter length or average diameter length of multiple particles. Similarly, the thickness is the median thickness or average thickness of multiple particles.
[0031] Exemplarily, the average diameter length and average thickness of the graphite oxide powder are 2 μm, 2 nm; 3 μm, 1 nm; 2 μm, 1 nm or 1 μm, 1 nm, respectively.
[0032] Compared with petroleum coke, the chitosan-based porous carbon used in this application performs poorly in mechanical strength (hardness). To alleviate this problem, this application adds graphite oxide powder with the above aspect ratio to the chitosan porous microsphere raw material, which can undergo amidation reaction with the amino group in chitosan through the carboxyl group to form a strong cross-linking bond, which can effectively compensate for the hardness of the prepared porous carbon, reduce the collapse and damage of the pore structure, and ensure the number of mesopores. At the same time, it effectively improves the conductivity of porous carbon. In addition, the distribution of graphite oxide powder in porous carbon can restrain the volume expansion of deposited silicon, which is beneficial to improve cycle stability.
[0033] It should be noted that the above aspect ratio is the ratio of the thickness of the graphite oxide powder to its diameter, and both the thickness and the diameter can be obtained by statistically analyzing at least 200 typical samples using a scanning electron microscope, a light scattering instrument, a light scattering instrument and other equipment.
[0034] In a second aspect, the present application provides a porous carbon prepared by any of the preparation methods described above.
[0035] In a third aspect, the present application provides a silicon-carbon negative electrode material, which is obtained by using the porous carbon obtained by any of the above-mentioned preparation methods as a raw material, and sequentially performing silane deposition and carbon source gas coating.
[0036] In any of the above technical solutions, the method for preparing the silicon-carbon negative electrode material is: The porous carbon obtained by any of the above methods is added into a fluidized bed reactor, and a silicon source gas is introduced to perform a chemical vapor deposition to deposit silicon on the porous carbon; then a carbon source gas is introduced to perform a secondary chemical vapor deposition to deposit carbon on the porous carbon.
[0037] In any of the above technical solutions, the silane gas is monosilane gas and / or disilane gas.
[0038] In any of the above technical solutions, the carbon source gas is one or more of methane, ethane, propane, acetylene, ethylene, and propylene.
[0039] In any of the above technical solutions, the temperature of the primary chemical vapor deposition is 700-900° C., the time is 2-10 hours, and the pressure of the silicon source gas is 0.1-1 MPa.
[0040] In any of the above technical solutions, the temperature of the secondary chemical vapor deposition is 600-800° C., the time is 1-5 hours, and the pressure is 0.1-0.5 MPa.
[0041] In summary, this application has the following beneficial effects: This application uses chitosan and nano-calcium carbonate as raw materials, and obtains porous carbon with a uniform and stable mesoporous structure through processes such as emulsification cross-linking, carbonization, and hydrofluoric acid treatment. It effectively improves the problems of excessively high micropore content (less than 2nm) and large specific surface area in traditional porous carbon, effectively enhances the conductivity of porous carbon, and its deposition and buffering effects on silicon, which helps to improve the first coulombic efficiency and cycle stability of silicon-carbon negative electrode materials.
[0042] Furthermore, the present application adds graphite oxide powder to the raw materials, which effectively compensates for the loss of mechanical strength of porous carbon caused by the use of chitosan-based porous carbon, and improves the conductivity and cycle stability of silicon-carbon negative electrode materials to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the SEM image of the porous carbon in Example 1-1 of the present application.
[0044] Figure 2 It is the SEM image of the porous carbon in Examples 1-6 of the present application.
[0045] Figure 3 It is the SEM picture of the porous carbon in Comparative Examples 1-2 of the present application.
[0046] Figure 4 This is a SEM image of the silicon-carbon negative electrode material in Comparative Example 2-1 of the present application. DETAILED DESCRIPTION
[0047] Preparation Example 1, a porous carbon-based material, the preparation method is as follows: Weigh 50g chitosan (deacetylation degree 85%) and place it in a 5000ml three-necked flask, add 1000ml acetic acid solution with a concentration of 2wt% and stir to dissolve, add 2500mL liquid paraffin, 20g spherical nano calcium carbonate (sphericity 0.9, particle size distribution 3-20nm), graphite oxide powder (average diameter 2μm, average thickness 2nm) and 30mL Span80, stir for 20min to obtain an emulsion system. Add 20mL of epichlorohydrin to the emulsion system, add an appropriate amount of sodium hydroxide solution under stirring conditions, and allow the emulsion system to undergo cross-linking reaction under alkaline conditions of pH 9. React for 1h, filter and wash to remove residual organic matter, place the product in an oven at 50℃ to dry to constant weight, grind, and obtain chitosan microspheres with an average particle size of about 12μm.
[0048] Under nitrogen protection, the chitosan microspheres were calcined and carbonized at 600±10°C for 4 h, cooled to room temperature, and carbonized microspheres were obtained and immersed in 4.5wt% hydrofluoric acid to remove the spherical nano-calcium carbonate. The microspheres were filtered, and the residual hydrofluoric acid and reactants were washed with deionized water. The microspheres were dried in an oven to constant weight to obtain porous carbon.
[0049] Preparation Example 2, a porous carbon-based material, the preparation method is as follows: Weigh 50g chitosan (80% deacetylation) into a 5000ml three-necked flask, add 1000ml 2wt% acetic acid solution and stir to dissolve, add 2200mL liquid paraffin, 18g spherical nano calcium carbonate (sphericity 0.85, particle size distribution 5-25nm), graphite oxide powder (average diameter 4μm, average thickness 2nm) and 35mL Span80, stir for 20min to obtain an emulsion system. Add 25mL epichlorohydrin to the emulsion system, add an appropriate amount of sodium hydroxide solution under stirring, and make the emulsion system cross-link under alkaline conditions of pH 9. React for 1h, filter and wash to remove residual organic matter, place the product in an oven at 50℃ to dry to constant weight, grind, and obtain chitosan microspheres with an average particle size of about 16 μm.
[0050] Under nitrogen protection, the chitosan microspheres were calcined and carbonized at 560±10°C for 5 h, cooled to room temperature, and carbonized microspheres were obtained and immersed in 4.5wt% hydrofluoric acid to remove the spherical nano-calcium carbonate. The microspheres were filtered, and the residual hydrofluoric acid and reactants were washed with deionized water. The microspheres were dried in an oven to constant weight to obtain porous carbon.
[0051] Preparation Example 3, a porous carbon-based material, the preparation method is as follows: Weigh 50g chitosan (90% deacetylation) into a 5000ml three-necked flask, add 1000ml 3wt% acetic acid solution and stir to dissolve, add 2600mL liquid paraffin, 23g spherical nano calcium carbonate (sphericity 0.95, particle size distribution 5-30nm), graphite oxide powder (average diameter 1μm, average thickness 1nm) and 40mL Span80, stir for 30min to obtain an emulsion system. Add 20mL epichlorohydrin to the emulsion system, add an appropriate amount of sodium hydroxide solution under stirring conditions, and allow the emulsion system to undergo cross-linking reaction under alkaline conditions of pH 9. React for 1h, filter and wash to remove residual organic matter, place the product in an oven at 50℃ to dry to constant weight, grind, and obtain chitosan microspheres with an average particle size of about 5μm.
[0052] Under nitrogen protection, the chitosan microspheres were calcined and carbonized at 630±10°C for 3 h, cooled to room temperature, and carbonized microspheres were obtained and immersed in 4 wt% hydrofluoric acid to remove the spherical nano-calcium carbonate. The microspheres were filtered, and the residual hydrofluoric acid and reactants were washed with deionized water. The microspheres were dried in an oven to constant weight to obtain porous carbon.
[0053] Preparation Example 4, a porous carbon-based material, differs from Preparation Example 1 in that an equal amount of spherical nano-calcium carbonate (sphericity 0.9, particle size distribution 3-20 nm) is used to replace graphite oxide powder (average diameter 2 μm, average thickness 2 nm).
[0054] Preparation Example 5, a porous carbon-based material, is different from Preparation Example 1 in that an equal amount of graphite powder (average diameter length 2 μm, average thickness 2 nm) is used to replace the oxidized graphite powder (average diameter length 2 μm, average thickness 2 nm).
[0055] Preparation Example 6, a porous carbon-based material, is different from Preparation Example 1 in that ethyl acetate is used to replace the spherical nano-calcium carbonate. The specific operation is as follows: Weigh 50g chitosan (85% deacetylation) in a 5000ml three-necked flask, add 1000ml 2wt% acetic acid solution and stir to dissolve, add 2500mL liquid paraffin, 35mL ethyl acetate, graphite oxide powder (average diameter 2μm, average thickness 2nm) and 30mL Span80, stir for 20min to obtain an emulsion system. Add 20mL epichlorohydrin to the emulsion system, add an appropriate amount of sodium hydroxide solution under stirring, and make the emulsion system undergo cross-linking reaction under alkaline conditions of pH 9. React for 1h, filter and wash to remove residual organic matter, place the product in an oven at 50℃ to dry to constant weight, grind, and obtain chitosan microspheres with an average particle size of about 12μm.
[0056] Under nitrogen protection, the chitosan microspheres were calcined and carbonized at 600±10°C for 4 h and cooled to room temperature to obtain porous carbon.
[0057] Preparation Example 7, a porous carbon-based material, is different from Preparation Example 1 in that an equal amount of chitosan with a deacetylation degree of 70% is used to replace chitosan with a deacetylation degree of 90%.
[0058] Preparation Example 8, a porous carbon-based material, is different from Preparation Example 1 in that an equal amount of chitosan with a deacetylation degree of 95% is used to replace chitosan with a deacetylation degree of 90%. Example
[0059] Example 1-1, a porous carbon, the preparation steps are as follows: Petroleum coke (median particle size 40 μm), potassium hydroxide, and the porous carbon of Preparation Example 1 were mixed in a mass ratio of 1:3.5:1 and stirred for 15 minutes to prepare 1 kg of a premix.
[0060] The premix is sent to the activation furnace, and in a nitrogen atmosphere, the temperature is raised to 350°C at a rate of 5°C / min, and the temperature is kept constant for 1 hour; then the temperature is raised to 800°C at a rate of 10°C / min, and the temperature is kept constant for 2 hours before being taken out of the furnace to obtain activated carbon. The potassium hydroxide in the activated carbon is extracted and dissolved with deionized water, and the activated carbon is separated by filtration and dried at 160°C, and the moisture content is controlled at 6-9%. The activated carbon is then air-flow-pulverized, and the median particle size is controlled at 6-8μm.
[0061] Example 1-2, a porous carbon, the preparation steps are as follows: Petroleum coke (median particle size 40 μm), potassium hydroxide, and the porous carbon of Preparation Example 2 were mixed in a mass ratio of 1:4:0.6 and stirred for 15 minutes to prepare 1 kg of a premix.
[0062] The premix is sent to the activation furnace, and in a nitrogen atmosphere, the temperature is raised to 300°C at a rate of 3°C / min, and the temperature is kept constant for 1 hour; then the temperature is raised to 700°C at a rate of 6°C / min, and the temperature is kept constant for 3 hours before being taken out of the furnace to obtain activated carbon. The potassium hydroxide in the activated carbon is extracted and dissolved with deionized water, and the activated carbon is separated by filtration and dried at 160°C, and the moisture content is controlled at 6-9%. The activated carbon is then air-flow-pulverized, and the median particle size is controlled at 6-8μm.
[0063] Example 1-3, a porous carbon, the preparation steps are as follows: Petroleum coke (median particle size 40 μm), potassium hydroxide, and the porous carbon of Preparation Example 3 were mixed in a mass ratio of 1:3:1.2 and stirred for 15 minutes to prepare 1 kg of a premix.
[0064] The premix is sent to the activation furnace, and in a nitrogen atmosphere, the temperature is raised to 400°C at a rate of 8°C / min, and the temperature is kept constant for 2 hours; then the temperature is raised to 900°C at a rate of 5°C / min, and the temperature is kept constant for 1 hour before being taken out of the furnace to obtain activated carbon. The potassium hydroxide in the activated carbon is extracted and dissolved with deionized water, and the activated carbon is separated by filtration and dried at 170°C, and the moisture content is controlled at 6-9%. The activated carbon is then air-flow-pulverized, and the median particle size is controlled at 6-8μm.
[0065] Example 1-4 is a porous carbon, which is different from Example 1-1 in that the porous carbon of Preparation Example 1 is replaced by an equal amount of the porous carbon of Preparation Example 4.
[0066] Example 1-5 is a porous carbon, which is different from Example 1-1 in that the porous carbon of Preparation Example 1 is replaced by an equal amount of the porous carbon of Preparation Example 5.
[0067] Example 1-6 is a porous carbon, which is different from Example 1-1 in that the porous carbon of Preparation Example 1 is replaced by an equal amount of the porous carbon of Preparation Example 6.
[0068] Example 1-7, a porous carbon, is different from Example 1-1 in that the porous carbon of Preparation Example 1 is replaced by an equal amount of the porous carbon of Preparation Example 7.
[0069] Example 1-8, a porous carbon, is different from Example 1-1 in that the porous carbon of Preparation Example 1 is replaced by an equal amount of the porous carbon of Preparation Example 8.
[0070] Comparative Example 1-1, a porous carbon, differs from Example 1-4 in that the porous carbon of Preparation Example 4 is replaced by an equal amount of petroleum coke.
[0071] Comparative Example 1-2 is a porous carbon, which is different from Example 1-4 in that the porous carbon of Preparation Example 4 is used to replace the petroleum coke in an equal amount.
[0072] Example 2-1, a silicon-carbon negative electrode material, the preparation method is as follows: The porous carbon of Example 1-1 was added to a fluidized bed reactor, monosilane gas was introduced, the silicon source gas pressure was 0.5 MPa, and a chemical vapor deposition was performed at 800°C, during which the silicon generated was deposited in the pores of the porous carbon. After 4 hours of deposition, a carbon source gas was introduced, and a secondary chemical vapor deposition was performed at a temperature of 680°C and a pressure of 0.2 MPa. During this period, the carbon generated was deposited on the surface of the porous carbon to form a coating layer. The deposition time was 2 hours, and a silicon-carbon negative electrode material was obtained.
[0073] Example 2-2, a silicon-carbon negative electrode material, the preparation method is as follows: The porous carbon of Example 1-2 was added to a fluidized bed reactor, monosilane gas was introduced, the silicon source gas pressure was 0.2 MPa, and a chemical vapor deposition was performed at 850°C, during which the silicon generated was deposited in the pores of the porous carbon. After 6 hours of deposition, a carbon source gas was introduced, and a secondary chemical vapor deposition was performed at a temperature of 750°C and a pressure of 0.3 MPa. During this period, the carbon generated was deposited on the surface of the porous carbon to form a coating layer. The deposition time was 1 hour, and a silicon-carbon negative electrode material was obtained.
[0074] Example 2-3, a silicon-carbon negative electrode material, the preparation method is as follows: The porous carbon of Example 1-3 was added to a fluidized bed reactor, monosilane gas was introduced, the silicon source gas pressure was 0.6 MPa, and a chemical vapor deposition was performed at 750°C, during which the silicon generated was deposited in the pores of the porous carbon. After 5 hours of deposition, a carbon source gas was introduced, and a secondary chemical vapor deposition was performed at a temperature of 650°C and a pressure of 0.1 MPa. During this period, the carbon generated was deposited on the surface of the porous carbon to form a coating layer. The deposition time was 3 hours, and a silicon-carbon negative electrode material was obtained.
[0075] Example 2-4, a silicon-carbon negative electrode material, differs from Example 2-1 in that the porous carbon prepared in Example 1-1 is replaced by an equal amount of porous carbon prepared in Example 1-4.
[0076] Example 2-5, a silicon-carbon negative electrode material, differs from Example 2-1 in that the porous carbon prepared in Example 1-1 is replaced by an equal amount of porous carbon prepared in Example 1-5.
[0077] Example 2-6, a silicon-carbon negative electrode material, differs from Example 2-1 in that the porous carbon prepared in Example 1-1 is replaced by an equal amount of porous carbon prepared in Example 1-6.
[0078] Example 2-7, a silicon-carbon negative electrode material, differs from Example 2-1 in that the porous carbon prepared in Example 1-1 is replaced by an equal amount of porous carbon prepared in Example 1-7.
[0079] Example 2-8, a silicon-carbon negative electrode material, differs from Example 2-1 in that the porous carbon prepared in Example 1-1 is replaced by an equal amount of porous carbon prepared in Example 1-8.
[0080] Comparative Example 2-1, a silicon-carbon negative electrode material, differs from Example 2-1 in that the porous carbon prepared in Example 1-1 is replaced with an equal amount of the porous carbon in Comparative Example 1-1.
[0081] Comparative Example 2-2, a silicon-carbon negative electrode material, differs from Example 2-1 in that the porous carbon prepared in Example 1-1 is replaced with an equal amount of the porous carbon in Comparative Example 1-2.
[0082] Experiment 1: Determination of BET specific surface area of porous carbon and total volume of 2-50 nm mesopores The BET specific surface areas of the porous carbons prepared in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-2 were measured by the BJH method, and the total volume V of the pores with a pore size of 2 nm to 50 nm was analyzed. PT Specifically, using a gas adsorption measurement device, 50 mg of porous carbon was placed in the device, heated and degassed at 350°C for 1 hour, and then nitrogen adsorption was performed at -196°C.
[0083] Test 2: Porous carbon hardness determination According to the provisions of JB / T 12721-2016, the hardness of a single porous carbon particle sample was tested using a nanoindenter (model: Hysitron TI 950). Before the test, the porous carbon powder was dispersed in epoxy resin and cured, and the cured resin was cut by ion polishing. A nanoprobe was used to press the single porous carbon particle, and the indentation depth on the particle surface was monitored to calculate the hardness of the single porous carbon particle. Five particles of the same group of samples were tested in parallel and the average value was taken to characterize the hardness of the porous carbon.
[0084] Test 3: Conductivity test The powder conductivity meter (model RK02-FT-8100A) is used to measure the conductivity of porous carbon powder online based on the four-probe test principle and GB / T1552-1995. A known amount of porous carbon powder is used to compress the volume to a set pressure value or pressure under hydraulic power.
[0085] Test 4: First coulombic efficiency and capacity retention test Using the silicon-carbon negative electrode material prepared in Examples 2-1 to 2-8 and Comparative Examples 2-1 to 2-2 as the negative electrode active material, 80g of the silicon-carbon negative electrode material, 10g of a binder (CMC / SBR), 10g of a conductive agent (conductive carbon black, SP) and 220mL of a solvent were stirred and mixed to prepare a negative electrode slurry, which was coated on a copper foil, and then dried, cold pressed and cut to obtain a negative electrode sheet; a metal lithium sheet was used as a counter electrode, LiPF6 was used as an electrolyte salt (the concentration in the electrolyte was 1 mol / L), and a polypropylene film was used as a separator to assemble a button battery, and then the first coulomb efficiency of the button battery was tested (0.1C / 0.1C).
[0086] The silicon-carbon negative electrode materials prepared in Examples 2-1 to 2-8 and Comparative Examples 2-1 to 2-2 were compounded with graphite to prepare negative electrode materials with a capacity of 500 mAh / g for a full battery 300-cycle performance test under the following test conditions: 2.75-4.2 V, room temperature, 1C / 1C. The prepared full battery has a ternary positive electrode material and LiPF6 electrolyte salt (concentration in the electrolyte is 1 mol / L).
[0087] Table 1. Test results of porous carbon performance
[0088] Table 2. Test results of silicon-carbon negative electrode materials performance
[0089] Combining the examples and comparative examples and Tables 1 and 2, it can be seen that compared with the porous carbon prepared with petroleum coke as raw material in Comparative Example 1-1, the porous carbon obtained by composite activation treatment of porous-based carbon and petroleum coke in Example 1-1 has an increased total mesopore volume and a decreased specific surface area, indicating that the number of mesopores in the porous carbon increases while the number of micropores decreases, and the corresponding silicon-carbon negative electrode material (Example 2-1) prepared is more excellent in the first coulomb efficiency and capacity retention rate (cycle stability). The reason may be that the number of mesopores in the porous-based carbon is large, while the micropore content is very small, which can not only reduce the electrolyte loss caused by the high specific surface area and ensure the first coulomb efficiency; it also helps the deposition of nano-silicon and effectively buffers its volume changes to ensure its capacity retention rate.
[0090] Combining the embodiments and comparative examples and Tables 1 and 2, it can be seen that compared with the porous carbon prepared with porous carbon as raw material in Comparative Example 1-2, the porous carbon obtained by composite activation treatment of porous carbon and petroleum coke in Example 1-1 has a decreased total mesopore volume and an increased specific surface area, but the corresponding silicon-carbon silicon-carbon negative electrode material (Example 2-1) is more excellent in the first coulombic efficiency and capacity retention rate (cycle stability). The reason may be that the degree of graphitization of petroleum coke is higher than that of porous carbon. Therefore, the porous carbon prepared in the embodiment has more outstanding hardness and conductivity. The higher hardness helps to restrain the volume expansion of silicon particles, reduce the shedding of negative electrode materials, and help to ensure cycle stability; and good conductivity helps to improve coulombic efficiency.
[0091] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing porous carbon, characterized in that: The porous carbon is used to prepare a silicon-carbon negative electrode material, and the preparation method comprises: Mix petroleum coke, alkaline activator and porous carbon in a mass ratio of 1:1.8-4.5:0.4-1.2 to prepare a premix; The premix is placed in a non-reactive atmosphere, and then activated, washed, dried, and crushed to obtain the premix; The porous carbon is obtained by carbonizing chitosan microspheres and treating them with hydrofluoric acid.
2. The method for preparing porous carbon according to claim 1, characterized in that: The porous carbon preparation method is as follows: Dissolve chitosan in a dilute acid solution, add liquid paraffin, spherical nano calcium carbonate, and an emulsifier, and stir to form an emulsion system; add epichlorohydrin to the emulsion system, and add an alkaline solution under stirring to allow the system to undergo cross-linking under alkaline conditions; After the reaction is completed, chitosan microspheres are obtained by filtering, washing and drying; the mass ratio of chitosan to spherical nano-calcium carbonate is 1:0.25-0.
4. Under nitrogen protection, the chitosan microspheres are calcined and carbonized at 550-650°C; the carbonized microspheres are then immersed in hydrofluoric acid to remove the spherical nano-calcium carbonate, and porous carbon is obtained by centrifugation, washing and drying.
3. The method for preparing porous carbon according to claim 1, characterized in that: The activation treatment is as follows: heating to 280-450°C at a rate of 1-10°C / min, and treating at a constant temperature for 1-2h; then heating to 700-900°C at a rate of 5-10°C / min, and treating at a constant temperature for 1.5-3.5h.
4. The method for preparing porous carbon according to claim 1, characterized in that: The alkaline activator is potassium hydroxide or sodium hydroxide.
5. The method for preparing porous carbon according to claim 1, characterized in that: The particle size distribution of the spherical nano calcium carbonate is 2-50 nm.
6. The method for preparing porous carbon according to claim 1, characterized in that: The median particle size of the porous carbon is 1 to 20 μm.
7. The method for preparing porous carbon according to claim 2, characterized in that: The deacetylation degree of the chitosan is 75-90%.
8. The method for preparing porous carbon according to claim 2, characterized in that: The emulsion system contains graphite oxide powder; the mass ratio of the chitosan to the graphite oxide powder is 1:0.05-0.15; and the aspect ratio of the graphite oxide powder is 1:500-5000.
9. A porous carbon, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. A silicon-carbon negative electrode material, characterized in that: The porous carbon obtained by the preparation method according to any one of claims 1 to 8 is used as a raw material, and silane deposition and carbon source gas coating are performed in sequence to obtain the porous carbon.
Citation Information
Patent Citations
Petroleum coke-based porous carbon material, preparation method thereof and silicon-carbon negative electrode material
CN109037679A